Strategi Pengembangan Wisata Pantai Kedungu, Kecamatan Kediri, Kabupaten Tabanan, Bali - anisa, nyoman; Restu, I Wayan -; Wijayanti, Ni Putu Putri (Bumi Lestari, 2021)
The purpose of this study is to find out the tourist attraction of Kedungu Beach as well as knowing Kedungu Beach Development Strategy with SWOT analysis. This research was conducted in January 2021, using descriptive and qualitative methods, as well as data analysis using SWOT analysis. The results obtained in this study are tourist attractions that are found on Kedungu Beach, there are natural beauties including the cleanliness of the beach water, photo spots, High waves that are suitable for surfing and beauty of the sunset in the afternoon Behind the natura beauty those owned by the Kedungu Beach tourist attraction, there are things that need to be considered, namely cleanliness environment of completeness of supporting facilities. The results of the SWOT analysis obtained a suitable strategi for the development of Kedungu Beach tourism, namely the SO (Stategy and Opportunities) strategy. Is a strategy that uses the power to take adventage of the strategy opportunities in question including improving the quality of human resources (human resources), opening services photographers for tourists whose reception is specifically for the surrounding community providing rental services surf tool. Keywords: Tourist Attraction, Kedungu Beach, , SWOT.